Graphene reinforced hydroxyapatite biocomposite coatings obtained by electrophoretic deposition on titanium - Marija Đošić; Ana Janković; Kyong Yop Rhee; Stanković Vesna Mišković (Zaštita Materijala)
Fast ongoing research of graphene-based nanomaterials reveals that their exceptional properties could be utized for biomedical applications, especially in tissue engineering and drug delivery. Here, we summarized the results obtained on hydroxyapatite based biocomposite coatings produced by electrophoretic deposition on titanium substrate and reinforced by nanosized graphene, as potential candidates for hard tissue implants.